Badanie uświadomionych potrzeb i barier edukacyjnych małych i średnich przedsiębiorstw w zakresie zarządzania jakością w celu ustalenia europejskiego standardu edukacji menedżera jakości w systemie studiów niestacjonarnych - analiza polskich doświadczeń i badań - Sujak-Cyrul, Barbara; Olejnik, Monika; Jednoróg, Adam; Sierzchuła, Zbigniew (Research on Small and Medium Enterprises' Conscious Educational Needs and Barriers in the Field of Quality Management for Purposes of Establishing European Standard of a Quality Managers Education in the Non-Stationary Studies System -Analysis of Polish Experiences and Results, 2008)
The paper presents experiences and outcomes of research resulting from the authors' works in the scope of European projecy EEFQUALITY MANAGEMENT as well as their own works connected with the subject – conducted both before and in parallel with the project – concerningsmall and medium enterprises' conscious educational needs and barriers in the field of quality management including quality management expert's profile perception by experienced practitioners in this filed. Results obtained in Poland, together with results obtained in Ireland, Spain, Sweden and Greece, will be used in the process of establishing European standard of a quality Manager's education in the non-stationary studies system, taking into account Lean and Six Sigma concepts.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 118-148